Creativity and change in Nigerian Christianity - Ogungbile, David O.; Akinade, Akintunde E. (Lagos : Malthouse Press ; Oxford : Distributed by African Books Collective, 2010)
In twenty-one illuminating chapters, the tenets and practice of Christianity in Africa and Nigeria are dissected in a path-breaking manner, covering theoretical issues in Christianity and change, practising pentecostalism and revivalism, performing and representing Christianity in arts and popular culture, encountering the Other, and Nigerian Christianity in other lands. It is a compulsory read for everyone. --Book Jacket.
Musings on the ebb and flow of world Christianity / Akintunde E. Akinade -- Creativity and change in Nigerian Christianity / David O. Ogungbile -- A bizarre exodus typology in Lk. 11, 20 / Ukachukwu Chris Manus -- Daughters of Ethiopia / Ogbu U. Kalu -- Authority in Pentecostalism / Joseph Kenny -- Interrogating the form and the Spirit / Pentecostalism and the Anglican Communion / Anthony O. Nkwoka -- Noise, fire, and flame / Dapo F. Asaju -- Reinhard Boonke's Crusades in Nigeria / Ezekiel Ajanai -- Youths and Pentecostalism / Essien Offiong -- Women and the politics of change / Dorcas O. Akitunde -- Women empowerment and Pentecostal experience / Oyeronke Olademo -- Healer-prophets and dynamics of power / Saibu A. Owoeye -- Privatization and commercialization of the Christian message / A. Olalekan Dairo -- Prosperity gospel and socail morality / Jacob K. Ayantayo -- Forms and functions of interrogation in charismatic Christian pulpit discourse / Rotimi Taiwo -- Musical revolution in contemporary Christianity / Femi Adedeji -- Evolutionary trends in Nigerian Christian drama / Foluke Ogunleye -- The turning tides of religious intolerance in Nigeria / Dogara J. Gwamna -- A history of Christian-Muslim relations in Nigeria / Musa A.B. Gaiya -- Interreligious dialogue in Nigeria / Joseph Kenny -- Faith without borders / David O. Ogungbile -- God@eBay : Nigerian churches in South Africa / Asonzeh Ukah.
Includes bibliographical references (p. [349]-357) and index.
Description based on print version record.
Keywords: Christianity -- Nigeria; Nigeria -- Church history; RELIGION / Christianity / History; Electronic books